Study of the epitaxy between ϵ‐Fe2O3, hematite and spinel in brown‐glazed Chinese ceramics using electron diffraction mapping techniques - Holé, Clément; Brunet, Magali; Joulié, Sébastien; Ren, Zhao; Wang, Tian; Wallez, Gilles; Sciau, Philippe (Journal of applied crystallography, 2024)
Black‐to‐brown Chinese ceramics have sparked the interest of material scientists since the widespread discovery of complex dendritic structures containing mainly the rare ϵ‐Fe2O3 polymorph in their glazes. This study proposes to tackle this issue using two electron diffraction mapping techniques, transmission Kikuchi diffraction and automated crystal orientation mapping–precession electron diffraction, which have not been fully exploited despite their relevance for studying these structures at the scales of interest. It first demonstrates the efficiency of applying these techniques to characterize the structures at the nanoscale and discusses some limitations that may be encountered, in particular due to the specificity of heritage samples. It then focuses on the crystalline orientations obtained with these techniques, which highlight epitaxial relationships among the crystalline planes (001) of the ϵ‐Fe2O3 phase, (0001) of the hematite and (111) of the spinel. Finally, it discusses the growth of such complex multi‐phase structures by proposing two possible mechanisms, one based on the transformation of ϵ‐Fe2O3 into hematite and spinel, and the other based on the growth of hematite and spinel on already crystallized ϵ‐Fe2O3 dendrites. It also compares the dendritic structures of the two modern samples with those found in an ancient sample of Jian ware. The possibilities of using transmission Kikuchi diffraction (TKD) to investigate historical materials are demonstrated through a study of ancient and recreated Chinese brown‐glazed ceramics. This work emphasizes the importance of understanding the complex crystalline structures found in glazes to document the growth mechanisms and tackles the specificities of studying such samples with TKD and automated crystal orientation mapping–precession electron diffraction.